2018
DOI: 10.1016/j.joen.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Response to RetroMTA after Partial Pulpotomy in Permanent Human Teeth

Abstract: This is the first work to evaluate a RetroMTA histologic outcome in partial pulpotomy in human permanent teeth. It shows pulp disorganization, an absence of inflammation, and discontinuous mineralization, which may represent a potential drawback with RetroMTA in this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…BioMTA shows similar composition to RetroMTA. Regarding RetroMTA, investigation in human teeth histologically showed disorganization of the pulp, dispersed mineralization, thin thickness of dentinal bridge in partial pulpotomies at eight weeks (13), and the new mineralized tissue did not exhibit regular dentin characteristics in direct pulp capping at seven months (14). However, these studies also reported good clinical/radiographic outcomes, which may be directly influenced by its physicochemical properties.…”
Section: Discussionmentioning
confidence: 98%
“…BioMTA shows similar composition to RetroMTA. Regarding RetroMTA, investigation in human teeth histologically showed disorganization of the pulp, dispersed mineralization, thin thickness of dentinal bridge in partial pulpotomies at eight weeks (13), and the new mineralized tissue did not exhibit regular dentin characteristics in direct pulp capping at seven months (14). However, these studies also reported good clinical/radiographic outcomes, which may be directly influenced by its physicochemical properties.…”
Section: Discussionmentioning
confidence: 98%
“…RetroMTA (BioMTA, Seoul, Korea) is a new hydraulic bioceramic material proposed for use in similar indications as MTA (pulp capping, perforations and root resorption repair, apexyfication and apical surgery) [27][28][29]. According to the manufacturer's product specification, the pH of RetroMTA is initially 12.5, and decreased to 7.8-8 in 4 weeks [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike MTA, this material does not contain Portland cement. RetroMTA has fast setting time (initial time of setting 150seconds), good handling properties, no cell toxicity, setting reaction initiated by moisture, no heavy metals, and greater washout resistance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction to vital signs, it supports that the pulp condition is healthy, leading to physiologic dentin deposition. Mass, E. et al reported that a calcified barrier was found in almost 70% of teeth [23], compared with 55%-64% in previous studies [24,25].…”
Section: Discussionmentioning
confidence: 79%